The impact of HLA-matching on reduced intensity conditioning regimen unrelated donor allogeneic stem cell transplantation for acute myeloid leukemia in patients above 50 years—a report from the EBMT acute leukemia working party. Issue 1 (December 2016) - Rubio, Marie; Savani, Bipin; Labopin, Myriam; Polge, Emmanuelle; Niederwieser, Dietger; Ganser, Arnold; Schwerdtfeger, Rainer; Ehninger, Gerhard; Finke, Jürgen; Renate, Arnold; Craddock, Charles; Kröger, Nicolaus; et al.
Abstract Background Data comparing fully matched and mismatched-unrelated-donor (M- and mM-URD) allogeneic hematopoietic stem cell transplant (allo-SCT) following reduced intensity conditioning regimens for acute myeloid leukemia are limited. Methods We retrospectively compared the outcome of 3398 patients above the age of 50 years who underwent 10/10 M-URD (n  = 2567), 9/10 (n  = 723), or 8/10 (n  = 108) mM-URD allo-SCT for acute myeloid leukemia after reduced intensity conditioning regimen between 2000 and 2013. The Kaplan-Meier estimator, the cumulative incidence function, and Cox proportional hazards regression models were used where appropriate. Results HLA matching had no impact on engraftment (p  = 0.31). In univariate analysis, in comparison to 10/10 M-URD, mM-URD was associated with higher incidence of grade II–IV acute graft-versus-host disease (GVHD) (p  = 0.0002), similar rates of chronic GVHD (p  = 0.138) but increased incidence of its extensive form (p  = 0.047). Compared to 10/10 M-URD, patients transplanted in the first complete remission (CR1) with a 9 or an 8/10 mM-URD had decreased 2-year leukemia free (LFS) (p  = 0.005) and overall survivals (OS) (56.7, 46.1, and 50.2 %, respectively, p  = 0.005), while outcomes were comparable between all groups for patients transplanted beyond CR1. In multivariate analysis, 9/10 versus 10/10 URD was associated with higher non-relapse mortality (HR 1.34, p  = 0.001), similar risk of relapse and chronic GVHD and inferior LFS (HR 1.25, p  = 0.0001), and OS (HR 1.27, p  = 0.0001). There was no difference in adjusted transplant outcomes between 9/10 and 8/10 mM-URD. Conclusions Reduced intensity conditioned allo-SCT with a 10/10 M-URD remains the preferable option for AML patients above the age of 50 years. The use of a 9/10 or an 8/10 mM-URD in patients not having a fully matched donor represents an alternative therapeutic option that should be compared to other alternative donor transplant strategies.